Problems and Solutions in the Production of Bitumen Emulsions: A Comprehensive Analysis - Sobir Sharipbaev; Nurbek Sharibaev; Nosir Sharibaev; Sherzod Djuraev (Zeta Repository, 2023)
Bitumen emulsions are widely used in various industries, particularly in road construction and maintenance, due to their numerous advantages. However, the production of bitumen emulsions can pose certain challenges that impact the quality and performance of the final product. This article provides a comprehensive analysis of the problems encountered in the production of bitumen emulsions and presents potential solutions to address these issues. The problems discussed include emulsion instability, poor adhesion, inadequate particle size distribution, and environmental concerns. The solutions encompass various aspects, such as the selection of suitable emulsifiers and additives, optimization of the emulsification process, and the utilization of innovative technologies. By understanding and addressing these challenges through effective solutions, manufacturers can improve the quality and performance of bitumen emulsions, leading to more sustainable and durable infrastructure solutions.